Paleoenvironment interpretation of a 1760 years B.P. old sediment in a mangrove area of the Bay of Guanabara, using pollen analysis - Barth,Ortrud M. (2006)
A sediment sample was obtained at 122 cm from the top of a drilling core in the Guapimirim mangrove, Bay of Guanabara, and analyzed using pollen analysis. This muddy core reached a sandy ground at 133 cm. 14C datation got the age of 1760 ± 50 years B.P. The most frequent pollen grains were mangrove species of Rhizophora mangle, Laguncularia racemosa and Avicennia schaueriana. "Restinga" and tropical rain forest vegetation was recognized behind the mangrove. After the last sea transgression at 2500 years B.P., the water level lowered to its actual size, allowing the installation of this mangrove.